Coupling effect between mechanical loading and chemical reactions - Klika, Václav; Marsík, Frantisek (The journal of physical chemistry. B, 2009)
This paper offers a theoretical explanation of the coupling effect phenomenon between mechanical loading and chemical reactions based on linear nonequilibrium thermodynamics and also discusses the classical method of obtaining restrictions on the phenomenological coefficients. The question whether static or dynamic loading influences biochemical processes is addressed-the necessity of dynamic loading as a stimulatory mechanism is shown. Further, the presented paper suggests that chemical and mechanical processes do not only facilitate or support one another but they may also play a triggering role for the other coupled process-some biochemical processes may need mechanical stimulation to run and vice versa as well-chemical reactions may provide energy for some mechanical processes. As an example, a detailed analysis of a model for controlled autocatalytic reproduction is presented, where the coupling effect, i.e. the influence of dynamic loading on reaction kinetics, is demonstrated.